2013
DOI: 10.1161/circulationaha.112.000799
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α 6 β 1 Is the Main Receptor for Vascular Laminins and Plays a Role in Platelet Adhesion, Activation, and Arterial Thrombosis

Abstract: Background-Laminins are major components of basement membranes, well located to interact with platelets upon vascular injury. Laminin-111 (α 1 β 1 γ 1 ) is known to support platelet adhesion but is absent from most blood vessels, which contain isoforms with the α 2 , α 4 , or α 5 chain. Whether vascular laminins support platelet adhesion and activation and the significance of these interactions in hemostasis and thrombosis remain unknown. Methods and Results-Using an in vitro flow assay, we show that laminin-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 30 publications
2
87
0
2
Order By: Relevance
“…α6β1 is a receptor for laminins (44), extracellular matrix components comprised of multiple isoforms whose expression varies in different tissues (45). α6 binding to laminins is thought to play an important role in platelet-mediated thrombosis (46). The role of α6 in lymphocyte trafficking, if any, remains to be determined; we have not seen alterations in lymphocyte homing to lymph nodes or Peyer's patches with an anti-α6 antibody that blocks laminin binding (Eugene C. Butcher, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…α6β1 is a receptor for laminins (44), extracellular matrix components comprised of multiple isoforms whose expression varies in different tissues (45). α6 binding to laminins is thought to play an important role in platelet-mediated thrombosis (46). The role of α6 in lymphocyte trafficking, if any, remains to be determined; we have not seen alterations in lymphocyte homing to lymph nodes or Peyer's patches with an anti-α6 antibody that blocks laminin binding (Eugene C. Butcher, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…1E,G). These isoforms were able to induce weak platelet aggregation in light transmission aggregometry (data not shown) and platelet adhesion (Schaff et al, 2013) indicating that they are, in principle, functional.…”
Section: Megakaryocytes Derived From Gp6mentioning
confidence: 93%
“…Moreover, we showed that transfusion of WT, but not α6-deficient, platelets partially restored metastasis in both thrombocytopenic and PF4-Cre-α6 -/-mice, confirming that the protective effect is platelet specific and does not rely on the absence of α6β1 integrin on any other cell type. In addition, we previously reported that platelets from PF4-Cre-α6 -/-mice expressed normal levels of the main adhesion receptors (21), further pointing towards a specific role for α6β1. Blood platelets express two additional members of the β1 integrin family, namely α2β1 and α5β1.…”
Section: Discussionmentioning
confidence: 83%
“…Of note, this blocking antibody did not provoke a thrombocytopenia, suggesting that such a pharmacological approach would preserve a normal platelet count. In addition, since platelet integrin α6β1 appears dispensable for normal hemostasis (21), one could hypothesize that targeting this integrin would also avoid bleeding complications. This is of importance since currently used antiplatelet drugs are known to increase the bleeding risk that complicates their use in clinical settings (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation